Translation, cultural adaptation, and validation of the German EMPATHIC-30G questionnaire for use in the neonatal intensive care setting - Odermatt, Katja; Roumet, Marie; Arnold, Christine; Burren, Juerg; Latour, Jos M.; Marston, Mark T.; Nagl-Cupal, Martin; Rippe, Ralph C. A.; Schwarz, Christoph E.; Simma, Alexander; Ferentzi, Hannah; Kidszun, André (Frontiers in Pediatrics, 2025)
BackgroundParental satisfaction is a key quality indicator in neonatal intensive care units (NICUs). While the EMPATHIC-30 questionnaire is widely used internationally, no validated German version exists for NICU settings. This study aimed to translate, culturally adapt, and validate the EMPATHIC-30G for use in German-speaking NICUs.MethodsA structured Delphi process involving multidisciplinary experts and parents guided the translation and cultural adaptation, including forward-backward translation and cognitive debriefing. The German version was validated in a prospective observational study at a Swiss NICU. Parents of infants hospitalized for ≥24 h completed the questionnaire at discharge.ResultsA total of 228 questionnaires were completed (138 by mothers, 89 by fathers, 1 by another caregiver). Exploratory factor analysis identified six latent factors for mothers and four for fathers, explaining ∼70% of variance. Internal consistency was excellent (McDonald's omega/Cronbach's alpha: 0.97/0.96 for mothers, 0.98/0.97 for fathers). Construct validity was supported by moderate to strong correlations with global satisfaction indicators; discriminant validity was confirmed by low correlation with unrelated variables. At the domain level, ceiling effects exceeded the 15% threshold across all five domains, though inter-item correlations remained acceptable. Several items showed substantial non-response due to being marked “not applicable” reflecting variability in clinical experiences.ConclusionThe EMPATHIC-30G is a reliable and valid instrument for assessing parent satisfaction in German-speaking NICUs. However, ceiling effects may limit its sensitivity in high-satisfaction settings. Further evaluation in multicenter samples is recommended.